DEMOCRATIC PROCESS AND POLITICAL CULTURE IN CENTRAL ASIAN STATES - Kumar , Hemant (CENTRAL ASIA AND THE CAUCASUS, 2024)
The paper is related to democratic process and political culture in Central Asian states. Democracy is strongly influenced by particular political cultures. Political culture articulates people’s rules and behaviour within their political world. Political culture influences how people see their political world and what they expect from it. For example, Alexis de Tocqueville, argued in his classic work “Democracy in America” that “American democracy was articulated by American values and attitudes”. In a democratic society, individual citizens have the power and right to influence decisions about how their country will be governed. According to the constitutions of the republics, they are sovereign, secular, and democratic republics. Sovereign means an independent nation. Secular implies freedom to choose your religion, which means the state gives every citizen the right to practice and propagate a religion of his choice, the state treats all religions as equal, and there is no official state religion. In a democracy, political parties act as the bridge between social thought and political decisions. After the disintegration of the Soviet Union, the independent Central Asian republics introduced a multi-party system, periodic elections, etc. to strengthen democracy. The emergence of political parties and groups in the region was the outcome of Mikhail Gorbachev's reform policy, called Glasnost and Perestroika. Central Asia has been able to sustain its democracy quite successfully with periodic elections and increasing active participation of people. The objective of this study is to examine the various models of democracy and political culture. This study focused on the role of the state (the constitution, political parties, election commission, parliament, judicial system, and fundamental rights) and non-state actors (citizens, social movements, and the media) in making the Central Asian democracy more vibrant.